Dentigerous Cyst Mimicking Odontogenic Keratocyst: A Rare Case Report with 12 Month Follow up - Rose M Joseph; Subhagatha Chakraborty; Anupama Nayak P; Dharnappa Poojary; Ashwin Rao; Nandita KP; Karuna YM (Institute of Medico-legal Publications Pvt Ltd, 2021)
Dentigerous cyst is one of the most commonly seen odontogenic cyst in children. It is characterized by aunilocular radiolucent lesion that encloses permanent tooth buds. Buccal bony expansion and a missing toothis the most common clinical feature. Various treatment modalities have been mentioned in the literature formanagement of dentigerous cysts. This case report presents the management of a left mandibular dentigerouscyst in a 10-year-old boy by surgical enucleation and its follow up.